Identities, characteristics, and assemblages of dematiaceous-endophytic fungi isolated from tissues of barnyard grassweed - Donayre, Dindo King M.; Dalisay, Teresita U. (2016)
Barnyard grass weed (Echninochloa glabrescens) in ricefields of Nueva Ecija, Philippines had been reported to harbor different isolates of endophytic fungi. Despite the discovery that its tissues are hosts to diverse endophytic fungi, the identities, characterisitics, and assemblages, particularly of the dematiaceous-endophytic fungi, are still unkown. This paper, thus, aimed to identify, and describe the characteristics and assemblages of the different dematiaceous-endophytic fungi that were isolated from tissues of barnyard grass weed of Nueva Ecija, Philippines. Microscopic examination revealed that there were eight common genera of dematiaceous-endophytic fungi residing in tissues of barnyard grass weed namely, Alternaria, Arthrinium, Bipolaris, Curvularia, Nigrospora, and Stemphyllium along with the two unidentified coded genera. Further examination of the taxonomic characteristics and assemblages showed that there were two species in the genus Alternaria (A. alternate and A. tenuidima) wile four for Bipolaris (B. australienses, Bipolaris sp. EF-ds102, B. avenacea, and Bipolaris rostrata), four for Curvularia (C. lunata, C. prasidii, C. pallescens, and Curvularia sp. EFds427), and two four Nigrospora (N. oryzae and Nigrospora sp. EF.ds180).
Keywords: Endophytic fungi